THE EFFECT OF ISLAMIC BOARDING SCHOOL ENVIRONMENT AND STUDENT LEARNING INTEREST ON STUDENT LEARNING OUTCOMES IN SOCIAL SCIENCES SUBJECTS - Albariki, Ahmad Yazid; Sunarto, Sunarto (Universitas Negeri Surabaya, 2020)
Student learning outcomes is a very important aspect in education because it is one indicator and benchmark of success in the teaching and learning process. Pesantren and students' interest in learning towards student learning outcomes in social studies subjects. Based on these objectives, this research uses quantitative methods. Researchers used multiple linear regression analysis with the help of SPSS 16.0 for Windows. Sampling in this study using probability sampling techniques with a total sample of 129 students. The results of this study indicate a significant fact between the environment of boarding schools and students' interest in learning towards student learning outcomes in social studies subjects.